Management behaviors during the COVID-19 pandemic: The case of healthcare middle managers - Mackay, Marie-Christine; Gilbert, Marie-Hélène; Fournier, Pierre-Sébastien; Dextras-Gauthier, Julie; Boucher, Frédéric (Frontiers in Psychology, 2022)
The spread of Covid-19 has disrupted the lifestyles of the world’s population. In the workplace, the pandemic has affected all sectors and has changed the way work is organized and carried out. The health sector has been severely impacted by the pandemic and has faced enormous challenges in maintaining healthcare services while providing care to those infected by the virus. At the heart of this battle, healthcare managers were key players in ensuring the orchestration of operations and the physical and mental availability of employees during the crisis. Although few studies have been conducted to identify organizational practices or leadership skills to be adopted in a crisis context, the concrete behaviors of managers have not been documented yet. Therefore, this study aims at filling this gap by studying middle managers’ behaviors facing COVID-19 crisis in the healthcare sector. Using a qualitative approach, eight focus groups were conducted online during the pandemic with 37 middle managers from the healthcare community of a Quebec health establishment (Canada) from April to June 2020. Thematic analyses were conducted, and a mixed-methods approach was used to analyze the data based on Viitala’s (2005) hierarchical model of management skills. Based on the six managerial skills proposed in the model of Viitala (2005), 21 specific management behaviors were identified as having been deployed by middle managers at the beginning of the pandemic. Considering that the health sector has been profoundly shaken by this health crisis, in addition to being an environment likely to experience other crises, managers need to develop practical skills in various crisis management situations. By identifying concrete management behaviors, these results could help to improve management training in a crisis context. Thus, this study allows practitioners to draw lessons to guide future behaviors of managers to prepare for possible situations while being more confident in their ability to manage different crises.